Effects of flood discharge on the water quality of a drinking water reservoir in China – Characteristics and management strategies. (15th July 2022) - Si, Fan; Huang, Tinglin; Li, Nan; Li, Kai; Wen, Gang; Li, Yang; Zhang, Haihan
Abstract: Stormflow runoff is an important non-point source of pollution in drinking water reservoirs. Rationally managed flood discharge processes at estuaries can reduce the high concentration of pollutants carried by runoff, and thus their impacts on water plant operations. In this study, the physical and chemical water quality parameters upstream from a dam were measured for a flood discharge process in the Jinpen Reservoir of Northwest China. The results showed that the time needed for the flood to reach the reservoir was ∼9 h after flooding began, and this lag effect meant that water in the metalimnion and hypolimnion were vented in advance. Consequently, the undercurrent intruded into the hypolimnion. The water temperature increased by 1.83 °C, and the Schmidt stability index decreased from 3291.37 J m −2 to 2496.32 J m −2 . Flood discharge can effectively reduce the volume of pollutants; however, it cannot completely prevent the deterioration of water quality in the main reservoir. The turbidity of the reservoir still exceeded 300 NTU after the flood discharge. When the outflow discharge decreased, the critical height of aspiration also decreased, and dissolved pollutants could neither be vented nor precipitated quickly, not allowing their concentration within the reservoir to decrease further. A three-dimensional hydrodynamic model was successfully used to simulate flood processes and determine an optimal flood discharge plan. We found that the elevations of the outlet and undercurrent layer are essential to determine the efficiency of flood discharge, while appropriate timing and outflow discharge volumes may further enhance the results. Therefore, using a hydrodynamic model to predict the position of an undercurrent layer, and opening spillways near the elevation of the undercurrent layer can improve the efficacy of flood discharge. Our findings provide novel insights that may be used to improve the operation and management of source water reservoirs. Highlights: Flood discharge can reduce rather than eliminate the deterioration of water quality caused by flooding. Flood discharge in advance reduce the density of hypolimnion and move the elevation of the undercurrent downward. More attention should be paid to dissolved pollutants when the outflow is reduced. The elevation of the outlet and undercurrent layer are the keys to determining the efficiency of flood discharge.